PENGARUH PROFITABILITAS, LIKUIDITAS, PERTUMBUHAN PENJUALAN, STRUKTUR AKTIVA DAN KEBIJAKAN DIVIDEN TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Nurul Anggun Farisa, 13.05.52.0111; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2017)
This study examined the effect of profitability, liquidity, sales growth, asset structure and dividend policy on capital structure. This research was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing company. The sampling method using purposive sampling the study period of 2012 to 2014. The relationship and influence between variables or described by using multiple regression analysis. The results showed that the liquidity and asset structure significant negative effect on the capital structure, sales growth significant positive effect on the capital structure. While profitability and dividend policy had no significant effect on the capital structure.Keywords: Profitability, Liquidity, Sales Growth, Structure Assets, Dividend Policy and Capital Structure